2023
DOI: 10.3389/fpubh.2023.1142602
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of lockdowns and restrictions during SARS-CoV-2 variant waves in the Canadian province of Nova Scotia

Abstract: IntroductionAfter the initial onset of the SARS-CoV-2 pandemic, the government of Canada and provincial health authorities imposed restrictive policies to limit virus transmission and mitigate disease burden. In this study, the pandemic implications in the Canadian province of Nova Scotia (NS) were evaluated as a function of the movement of people and governmental restrictions during successive SARS-CoV-2 variant waves (i.e., Alpha through Omicron).MethodsPublicly available data obtained from community mobilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Further investigation into the association between transit station mobility and COVID-19 cases demonstrated interesting insights. The epidemiological transmission of COVID-19 in Rwanda revealed a significant number of cases and deaths, with the highest numbers recorded and largest spikes in cases during the Delta variant period, which was similarly observed in South Africa ( 36 ) and Africa on a continental level ( 37 ), however, this was not the case in Canada ( 10 ) and Europe on a continental level ( 37 ), where the cases peaked during successive waves of Omicron and its sub-lineages (B.1.1.529, BA.4/0.5, XBB.1.5).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Further investigation into the association between transit station mobility and COVID-19 cases demonstrated interesting insights. The epidemiological transmission of COVID-19 in Rwanda revealed a significant number of cases and deaths, with the highest numbers recorded and largest spikes in cases during the Delta variant period, which was similarly observed in South Africa ( 36 ) and Africa on a continental level ( 37 ), however, this was not the case in Canada ( 10 ) and Europe on a continental level ( 37 ), where the cases peaked during successive waves of Omicron and its sub-lineages (B.1.1.529, BA.4/0.5, XBB.1.5).…”
Section: Discussionmentioning
confidence: 88%
“…To remove seasonal aspects of the data, we selected the records of Rwanda on a seven-day basis. Martinez and Kelvin ( 10 ) compared mobility data gathered from distinct tech companies and conclude the data is highly correlated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, it was suggested that the early introduction of the B.1.1.529 (ie, Omicron) SARS-CoV-2 variant in Mexico was facilitated by higher movement observed in the end-of-year celebrations [ 5 ]. Moreover, in Canada, a so-called successful pandemic management was attributed to the fact that the movement patterns of people were highly reduced during the initial waves of SARS-CoV-2 [ 6 ]. Higher transmission of SARS-CoV-2 in India was attributed to an urban exodus of city dwellers that had to return to their villages after lockdown policies were implemented [ 7 ].…”
Section: Introductionmentioning
confidence: 99%